#-6/7#
Step 1) Solve for the parenthesis/ brackets "( )" in the equation
#3x+5-6(x+1)=4x+5#
Becomes:
#3x+5-6x-6=4x+5#
Step 2) Put the variables (in this case, #x#) on one side of the equal sign and the real numbers on the other side.
#3x-6x-4x=5+6-5# (putting the variable on the left side of the equal sign is preferable)
Step 3) Solve:
#-7x=6#
#x=-6/7#
How do you solve #3x + 5- 6( x + 1) = 4x + 5#?
Coins can be redeemed for fabulous gifts.
Log In
Sign Up
Post an Article
Post an Answer
Post a Question with Answer
Contribute Homework Answers ($1+ Per Post)